Association of Cord Blood Total Protein and Albumin Levels with Respiratory Distress Syndrome - Behzad Barekatain; Amir-Mohammad Armanian; Armin dokht Shahsanaei; Marjaneh Shokrani Chaharsoughi (Mashhad University of Medical Sciences, 2020)
Background: Respiratory distress syndrome (RDS) is one of the major causes of morbidity and mortality in preterm newborns. The severity and treatment of RDS affect the outcomes of premature neonates in neonatal intensive care units. Some studies have claimed that hypoalbuminemia and hypoproteinemia are associated with poorer outcomes in preterm neonates. The current study aimed to assess the association of serum total protein and albumin with the presentation of RDS among this group of newborns.Methods: This cross-sectional study was carried out on a total of 100 preterm newborns. The study population included a control group of healthy neonates (n=50) and case group of newborns diagnosed with RDS (n=50). For each neonate, a 2 ml sample of the arterial blood was taken from the umbilical artery, and laboratory indices, including total serum protein and albumin, were measured. Statistical analysis was conducted to compare potential variations between the samples of the healthy and RDS groups.Results: According to the obtained findings, no statistical difference was observed between the healthy and RDS preterm neonates regarding total protein (P=0.16) and serum albumin (P=0.27) levels. Total serum protein and albumin were not affected by the newborn's birth weight and gender (P>0.05) among both the healthy preterm neonates and those with RDS. However, a significant association was observed regarding gestational age (P<0.05) for both the healthy and RDS neonates and maternal age for the healthy neonates only (P<0.05).Conclusion: No difference was observed in total serum protein and albumin levels between the healthy preterm neonates and those with RDS. Furthermore, total serum protein and albumin levels were not affected by gender, birth weight, and maternal age among the RDS patients. However, they were directly associated with the gestational age at the time of birth in both the RDS and healthy groups.